2019
DOI: 10.1515/cclm-2019-1248
|View full text |Cite
|
Sign up to set email alerts
|

Mixing studies for lupus anticoagulant: mostly no, sometimes yes

Abstract: Mixing tests have long been a mainstay in the lupus anticoagulant (LA) testing armoury of screen, mix and confirm assays. If a sample with an elevated screening test does not evidence inhibition in the mixing test, the search for an LA is halted and a different diagnostic pathway embarked upon. Recent years have seen studies evidencing sometimes high frequencies of false-negative mixing tests with perhaps sinister implications for missed diagnoses and skewed patient management. Issues such as the dilution effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…35,58,60 The need for mixing tests is reflected in the affirmative response of majority of the ISTH-SSC survey respondents (84.1%) and recent literature. 15,61,62 Mixing tests are commonly performed on screening assays. A mixing test in the confirmatory step can be performed if the confirmatory clotting time on undiluted plasma is prolonged.…”
Section: Three Step Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…35,58,60 The need for mixing tests is reflected in the affirmative response of majority of the ISTH-SSC survey respondents (84.1%) and recent literature. 15,61,62 Mixing tests are commonly performed on screening assays. A mixing test in the confirmatory step can be performed if the confirmatory clotting time on undiluted plasma is prolonged.…”
Section: Three Step Proceduresmentioning
confidence: 99%
“…More recent studies illustrate that omitting the mixing step may give false‐positive and false‐negative results 35,58,60 . The need for mixing tests is reflected in the affirmative response of majority of the ISTH‐SSC survey respondents (84.1%) and recent literature 15,61,62 …”
Section: Preanalytical Analytical and Postanalytical Factors In La Tmentioning
confidence: 99%
“…41 Although single positivity is associated with fewer clinical events and less recurrence, single positivity via LA can be clinically significant. 2,66 Particularly for patients anticoagulated with VKAs, where mixing tests with dRVVT and APTT can generate false-negatives, [4][5][6][7]15,16 TSVT/ET provides a viable route to detection of LA in single-positive patients when anticoagulated with VKAs or DFXaIs. The lack of correlation between INR and TSVT ratio was unsurprising given the ability of oscutarin C to activate descarboxyprothrombin.…”
Section: The Oscutarin C Fraction Of Coastal Taipan (Oxyuranus Scutel...mentioning
confidence: 99%
“…7,14 The main approaches are mixing tests to correct the effects of vitamin K antagonists (VKA), [5][6][7]15 reagent-integral heparin neutralisers, 13 and preanalytical removal of direct oral anticoagulants (DOAC) from plasma using adsorbent material. 10 However, mixing tests reduce sensitivity to LA, 7,16 heparin neutralizers are effective only up to a certain level of heparin, 13 and incomplete removal and assay interferences in samples from non-DOAC treated patients have been reported with DOAC adsorbents. 17 Assays employing snake venom prothrombin activators that are insensitive to the effects of VKAs, and by design will bypass direct factor Xa inhibitors (DFXaI), have been described but are not widely used, partly because of limited availability of standardized reagents.…”
Section: Introductionmentioning
confidence: 99%
“…We have not performed mixing studies as suggested in ISTH guidance because of a lack of available plasma; likewise, factor assays have not been assessed because the Dade Actin FS APTT has been assessed for each patient to ensure no prolongation has been noted. 7 , 23 , 24 We have not correlated the assay results with clinical details of the patient samples (e.g., presence of cardiolipin/beta‐2‐glycoprotein I antibodies and history of obstetric morbidity/thrombosis) and we have no prior knowledge of their LA status off anticoagulation previously. This study did not aim to correlate the assays with patient phenotype but investigated the assay performance for DOAC Remove plus dRVVT/APTT versus TSVT/ET.…”
Section: Discussionmentioning
confidence: 99%